ENHANCING QUR'ANIC TADABBUR SKILLS OF AL-KHOLIFAH STUDENTS THROUGH SEMITIC RHETORIC - Asnawi, Aqdi Rofiq; Al Madani, Muhammad Dini Syauqi; Ramadhani, Mulyo Rizky (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
The rapid advancement of technology has resulted in a significant decline in the quality of tadabbur (deep contemplation) of the Qur'an, particularly among the younger generation. This decline is predominantly influenced by technological developments and the pervasive use of social media, which frequently divert children's attention from reflective and spiritual activities. These challenges are compounded by a lack of proficiency in classical Arabic and insufficient guidance in contextualizing Qur'anic messages within contemporary issues. In response to these issues, this community service initiative employs a Semitic rhetorical approach aimed at enhancing tadabbur skills at the Qur'anic Learning Center of Taman Pendidikan Al-Qur’an (TPA) Al-Kholifah Sekaran, Ponorogo, with a focus on QS. Al-'Alaq. The methodological framework for this program includes stages of preparation, implementation, and evaluation. The evaluation outcomes reveal a substantial improvement in students' comprehension of both tadabbur and Semitic rhetoric, with the average score increasing from 34% to 84%. These results demonstrate that the integration of a Semitic rhetorical approach not only deepens students' understanding of QS. Al-'Alaq but also strengthens their spiritual engagement with the Qur'an, providing a more solid foundation for addressing life's challenges. This program underscores the critical importance of incorporating comprehensive learning methodologies within Islamic education to effectively internalize Qur'anic values.